A Contrast in Abstracts: The Discerning Indian Eye and Corporate Art - Kapil Chowdhury (International Journal of Control and Automation, 2019)
A nonverbal means of expression, art may move audiences beyond the limitations of language. It’s a great way for businesses to show their personalities, try out new ideas, and prove they’ve been paying attention. Purchasing artwork for your firm may improve morale, inspire employees, and make the workplace more pleasant to spend time in. A better experience is achieved when a company’s basic values are communicated to its workers, customers, and suppliers via the example provided by the company’s leadership. Customers’ attention is captured, the firm is remembered, and its brand is set apart via the use of striking visuals. If you have customers or patients that regularly attend meetings or appointments, decorating with art may be a great way to break the ice and make everyone feel more at ease. With the rise of remote and hybrid workplaces, artwork may serve as a welcome diversion during otherwise tedious video conferences. These days, art can be an integral part of any successful business. In addition to its aesthetic value, art has the potential to promote sentiments of safety and unity among individuals by appealing to their sense of shared identity. Having a polished and professional image is essential for every business. It shows that you’re serious about your company and care about your clients, staff, and visitors. The confidence of the customers will increase when conducting business.